2022
DOI: 10.3389/fpsyt.2021.787792
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Domestic Violence Using Text Mining Outputs From Australian Police Records

Abstract: In Australia, domestic violence reports are mostly based on data from the police, courts, hospitals, and ad hoc surveys. However, gaps exist in reporting information such as victim injuries, mental health status and abuse types. The police record details of domestic violence events as structured information (e.g., gender, postcode, ethnicity), but also in text narratives describing other details such as injuries, substance use, and mental health status. However, the voluminous nature of the narratives has prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…Further, apart from those codes indicating presentations due to psychoactive substance abuse, the recorded codes referred to medical reasons for hospitalization that were unlikely related to domestic violence. This supports the idea that hospitals only see a small fraction of conditions arising from domestic violence situations or do not screen admitted individuals for domestic violence [37,38], which are recognized as limitations of the current domestic violence surveillance [36].…”
Section: Future Implicationssupporting
confidence: 75%
See 2 more Smart Citations
“…Further, apart from those codes indicating presentations due to psychoactive substance abuse, the recorded codes referred to medical reasons for hospitalization that were unlikely related to domestic violence. This supports the idea that hospitals only see a small fraction of conditions arising from domestic violence situations or do not screen admitted individuals for domestic violence [37,38], which are recognized as limitations of the current domestic violence surveillance [36].…”
Section: Future Implicationssupporting
confidence: 75%
“…Our findings indicated that the NSWPF encounter myriad mental illnesses in the context of domestic violence with more than 120 types identified [32,34]. This further demonstrates the usefulness of employing police narrative data for surveillance and monitoring purposes as we have previously suggested [36].…”
Section: Future Implicationssupporting
confidence: 70%
See 1 more Smart Citation
“…Чотири найпоширеніші психічні захворювання (зловживання алкоголем, біполярний розлад, депресія, шизофренія)однаково притаманні потерпілим як чоловічої, так і жіночої статі. Однак у жінок-жертв частіше спостерігається депресія (Karystianis et al, 2022).…”
Section: матеріали та методиunclassified